Pain in Adolescence: Maternal and Paternal Factors Affecting Adolescents' Pain in Norway-A Cross-Sectional Study - Erik Grasaas; Hilde Timenes Mikkelsen; Kristin Haraldstad; Sølvi Helseth; Milada Cvancarova Småstuen; Siv Skarstein; Gudrun Elin Rohde (MDPI AG, 2023)
Background: Pain in adolescence is considered a worldwide concern. Adolescents' pain affects family functioning. However, bidirectional associations should be considered as parental determinates such as pain, stress, and sociodemographic factors are also shown to influence pain in adolescence. Objectives: This study explored the associations between maternal and paternal sociodemographic factors, pain, and stress and adolescents' pain, and stress on adolescents' pain. Methods: In total, 508 school-based Norwegian adolescents with a corresponding parent were included. All adolescents completed an electronic survey during school hours, and their respective parents responded electronically. The survey included sociodemographic data, the Perceived Stress Questionnaire, and the Brief Pain Inventory. Results: Herein, 385 adolescents reported an average pain of 2.1 (SD, 1.9), and 308 of the participating parents reported an average pain of 1.6 (SD, 1.8). Regressions stratified by parental gender revealed nonsignificant associations in fathers' study variables predicting adolescents' pain. However, having the highest maternal educational level (p ≤ 0.01) and working part-time (p ≤ 0.01) were associated with lower pain in adolescents. Conclusions: The findings of this study demonstrated that sociodemographic factors such as high educational status in mothers and mothers working part-time were associated with lower pain in Norwegian adolescents. These findings highlight the importance of a holistic approach to pain management in adolescence.